Assessing the application of trace metals as paleoproxies and a chemostratigraphic tool in carbonate systems: A case study from the "Mississippian Limestone" of the midcontinent, United States. (February 2020) - Steinmann, J.W.; Grammer, G.M.; Brunner, B.; Jones, C.K.; Riedinger, N.
Abstract: Trace metals have been successfully used to reconstruct geochemical seawater conditions of both modern and ancient environments. The majority of these efforts have been limited to marine shales, with little work on carbonate systems. Applying similar methods of trace metal analysis on carbonate-dominated rocks may provide valuable insight into the paleoseawater chemistry, such as redox state, and productivity, of ancient carbonate systems. This study evaluates the application of trace metals as paleoproxies in carbonate rocks. Middle-ramp wackestones to grainstones from the "Mississippian Limestone" in the Midcontinent were analyzed using inductively-coupled plasma mass spectrometry (ICP-MS) for both the carbonate-fraction and the bulk-fraction trace metal content. Our data show that productivity proxies, such as Cd and P, are captured within the carbonate-fraction and may reflect seawater chemistry of the system. High Cd, and moderate bionutrient (P, Ni, Zn) enrichments indicate primary productivity in the system, though it is difficult to quantify to what extent. Vanadium, Cr, U, and Mo appear to be primarily associated with the bulk-fraction content and correlate well with Al content, indicating a detrital origin. Furthermore, V, U, and Mo show no significant enrichments, and Mo/Fe ratios correlate with those of shales from a modern oxic shelf. This suggests that anoxic or euxinic conditions in the water column were not present. Trace metal content of carbonate rocks have the potential to be used in paleoenvironmental reconstruction of carbonate systems, though challenges exist such as the lack of comparable carbonate trace metal data, bias of trace metal incorporation pathways into carbonates, and diagenetic alteration. Highlights: Cd, P, Ni, and Zn enrichments indicate primary productivity in the system. Cd and P are reflected within the carbonate-fraction and reflect seawater chemistry. V, U, and Mo abundances and Mo/Fe ratios suggest that oxic conditions were present. V, Cr, U, and Mo associate with the bulk-fraction content and correlate with Al. Trace metal content has the potential to be used as a chemostratigraphic tool in carbonate systems.